Scope of claim coverage in patents of fufang Chinese herbal drugs: Substitution of ingredients - Tian Jiaher; Wang Xinsheng; Chan Albert (BMC, 2011)
Abstract Herbal ingredients in a Chinese fufang prescription are often replaced by one or several other herbal combinations. As there have been very few Chinese herbal patent infringement cases, it is still unclear how the Doctrine of Equivalents should be applied to determine the scope of 'equivalents' in Chinese fufang prescriptions. Case law principles from cases in other technical areas such as chemical patents and biological drug patents can be borrowed to ascertain a precise scope of a fufang patent. This article summarizes and discusses several chemical and biopharmaceutical patent cases. In cases where a certain herbal ingredient is substituted by another herb or a combination of herbs, accused infringers are likely to relate herbal drug patents to chemical drug patents with strict interpretation whereas patent owners may take advantage of the liberal application of Doctrine of Equivalence in biopharmaceutical patents by analogizing the complex nature of herbal drugs with biological drugs. Therefore, consideration should be given to the purpose of an ingredient in a patent, the qualities when combined with the other ingredients and the intended function. The scope of equivalents also depends on the stage of the prior art. Moreover, it is desirable to disclose any potential substitutes when drafting the application. Claims should be drafted in such a way that all foreseeable modifications are encompassed for the protection of the patent owner's intellectual property.